The Likely Impact of Microinsurance on India’S Poor- a View of the Next 10 Years: Exploring the Potential of Microinsurance for India's Rural Poor (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The present paper discusses microinsurance in the contextof India. It has started with discussing the concept of microinsurance and itsimportance to poor people living in rural or remote areas. The paper furtherexplores the microinsurance situation in India. The paper reveals that even ifmicroinsurance sector has not obtained as much popularity as the traditionalinsurance, it is growing at a rapid pace. At present, the demand formicroinsurance is not very high in rural India due to lack of awareness andacceptance among poor people. However, microinsurance providers like insurancecompanies and government are trying to raise awareness of microinsurance.Hence, the future of this sector looks very bright and it will create positiveimpact on the lives of rural poor in future.